2021
DOI: 10.1038/s41598-021-81561-5
|View full text |Cite
|
Sign up to set email alerts
|

Post-collisional mantle delamination in the Dinarides implied from staircases of Oligo-Miocene uplifted marine terraces

Abstract: The Dinarides fold-thrust belt on the Balkan Peninsula resulted from convergence between the Adriatic and Eurasian plates since Mid-Jurassic times. Under the Dinarides, S-wave receiver functions, P-wave tomographic models, and shear-wave splitting data show anomalously thin lithosphere overlying a short down-flexed slab geometry. This geometry suggests a delamination of Adriatic lithosphere. Here, we link the evolution of this continental convergence system to hitherto unreported sets of extensively uplifted O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Continental lithospheric delamination has also become central to tectonic models for the Neogene evolution of the Alboran Sea (Platt and Vissers, 1989;Docherty and Banda, 1995;Seber et al, 1996;Molnar and Houseman, 2004;Duggen et al, 2005;Pérouse et al, 2010;De Lis Mancilla et al, 2013;Timoulali et al, 2014;Baratin et al, 2016;Heit et al, 2017;Spakman et al, 2018), although for counter arguments see Doglioni et al (1997). Continental lithospheric delamination has also entered the debate over the formation of the Pannonian Basin (Knapp et al, 2005;Houseman and Gemmer, 2007;Bennett et al, 2008;Lorinczi and Houseman, 2009;Matenco and Radivojević, 2012;Balling et al, 2021) and the Aegean Sea (Mantovani et al, 1997;van Hinsbergen et al, 2005;Roure et al, 2012). In the context of the Tyrrhenian Sea, Channell and Mareschal (1989) applied finite element analysis to demonstrate that continental mantle lithospheric delamination, triggered by localized lithospheric thickening, can rapidly change a region of compression into a region of extension, and that the extension can drive further shortening in a surrounding thrust belt.…”
Section: Subduction Of Continental Mantle Lithosphere Beneath the Tyr...mentioning
confidence: 99%
“…Continental lithospheric delamination has also become central to tectonic models for the Neogene evolution of the Alboran Sea (Platt and Vissers, 1989;Docherty and Banda, 1995;Seber et al, 1996;Molnar and Houseman, 2004;Duggen et al, 2005;Pérouse et al, 2010;De Lis Mancilla et al, 2013;Timoulali et al, 2014;Baratin et al, 2016;Heit et al, 2017;Spakman et al, 2018), although for counter arguments see Doglioni et al (1997). Continental lithospheric delamination has also entered the debate over the formation of the Pannonian Basin (Knapp et al, 2005;Houseman and Gemmer, 2007;Bennett et al, 2008;Lorinczi and Houseman, 2009;Matenco and Radivojević, 2012;Balling et al, 2021) and the Aegean Sea (Mantovani et al, 1997;van Hinsbergen et al, 2005;Roure et al, 2012). In the context of the Tyrrhenian Sea, Channell and Mareschal (1989) applied finite element analysis to demonstrate that continental mantle lithospheric delamination, triggered by localized lithospheric thickening, can rapidly change a region of compression into a region of extension, and that the extension can drive further shortening in a surrounding thrust belt.…”
Section: Subduction Of Continental Mantle Lithosphere Beneath the Tyr...mentioning
confidence: 99%
“…Similarly, the extent of the Dinaric slab at ~30 Ma is largely debated. Post-collisional uplift and contemporaneous emplacement of igneous rocks (33-22 Ma) in the internal Dinarides may suggest either 1) "that the Oligocene-Miocene orogen-wide uplift was driven by post-break-off delamination of the Adriatic lithospheric mantle" Balling et al (2021), or 2) verticalization of the Adria slab driven by slab pull and consequent upper plate extension, which is exactly what is modeled in our Model CWM. In conclusion, the available geophysical and geological data do not allow to discriminate between a model of post-collisional slab break-off and one of post-collisional slab verticalization (as modelled for the Alps and Dinarides in our Model CWM), as both would imply upper plate extension, uplift and magma emplacement (Faccenda et al, 2008(Faccenda et al, , 2009.…”
Section: How Well Does Model Cwm Fit Seismological Observations?mentioning
confidence: 64%
“…Evidence in favor of this model was provided by Casale et al (2013), who showed that the Mid-Bosnian Schist Mountains, located further externally with respect to Cer, also represent a MCC that was exhumed between 43 and 27.5 Ma, with rapid cooling occurring between 35 and 27 Ma-coincident with the timing of slab-breakoff and subsequent mantle delamination proposed by Pamić et al (2002) and Schefer et al (2011). This hypothesis is further supported by evidence for regional uplift during Oligocene times (Balling et al, 2021).…”
Section: Regional Implicationsmentioning
confidence: 71%